(untitled) (La U Investiga, 2023)
From topics focused on ICT Education; digital resources in educational contexts; educational experiences of attention NEAE and SEN with ICT; innovative methodologies with ICT for attention to diversity, inclusion and equity, which with ICT are developing a differentiating role in inclusion and reveal awareness of the digital gap and / or the educational gap with respect to the diversity of social groups; a work of 693 is presented.